Colonic bacterial composition in Parkinson's disease - Keshavarzian, Ali; Green, Stefan J.; Engen, Phillip A.; Voigt, Robin M.; Naqib, Ankur; Forsyth, Christopher B.; Mutlu, Ece; Shannon, Kathleen M. (Movement disorders, 2015)
Introduction We showed that Parkinson's disease (PD) patients have alpha‐synuclein (α‐Syn) aggregation in their colon with evidence of colonic inflammation. If PD patients have altered colonic microbiota, dysbiosis might be the mechanism of neuroinflammation that leads to α‐Syn misfolding and PD pathology. Methods Sixty‐six sigmoid mucosal biopsies and 65 fecal samples were collected from 38 PD patients and 34 healthy controls. Mucosal‐associated and feces microbiota compositions were characterized using high‐throughput ribosomal RNA gene amplicon sequencing. Data were correlated with clinical measures of PD, and a predictive assessment of microbial community functional potential was used to identify microbial functions. Results The mucosal and fecal microbial community of PD patients was significantly different than control subjects, with the fecal samples showing more marked differences than the sigmoid mucosa. At the taxonomic level of genus, putative, “anti‐inflammatory” butyrate‐producing bacteria from the genera Blautia, Coprococcus, and Roseburia were significantly more abundant in feces of controls than PD patients. Bacteria from the genus Faecalibacterium were significantly more abundant in the mucosa of controls than PD. Putative, “proinflammatory” Proteobacteria of the genus Ralstonia were significantly more abundant in mucosa of PD than controls. Predictive metagenomics indicated that a large number of genes involved in metabolism were significantly lower in the PD fecal microbiome, whereas genes involved in lipopolysaccharide biosynthesis and type III bacterial secretion systems were significantly higher in PD patients. Conclusion This report provides evidence that proinflammatory dysbiosis is present in PD patients and could trigger inflammation‐induced misfolding of α‐Syn and development of PD pathology. © 2015 International Parkinson and Movement Disorder Society